Prevention of violence against women in household by the Indonesian laws - Arief, Hanafi (Opción, 2019)
This study will analyze in depth the prevention of violence in household undertaken by the Indonesian government through the laws. This is a normative legal research with descriptive analysis. The results of the research show that in the prevention of domestic violence, Indonesian government has used a specific law and regulation such as Domestic Violence Law 23 of 2004 based on the Declaration of UNO on the Elimination of Discrimination against Women. In conclusion, to prevent violence in household, Indonesia also has used other related laws such as: Marriage Law 1 of 1974, and Human Rights Law 39 of 1999.